Phytotoxic Activities of Mediterranean Essential Oils - Rolim de Almeida, Luiz Fernando [UNESP]; Frei, Fernando [UNESP]; Mancini, Emilia; De Martino, Laura; De Feo, Vincenzo (Molecular Diversity Preservation International-mdpi, 2010)
Twelve essential oils from Mediterranean aromatic plants were tested for their phytotoxic activity, at different doses, against the germination and the initial radicle growth of seeds of Raphanus sativus, Lactuca sativa and Lepidium sativum. The essential oils were obtained from Hyssopus officinalis, Lavandula angustifolia, Majorana hortensis, Melissa officinalis, Ocimum basilicum, Origanum vulgare, Salvia officinalis and Thymus vulgaris (Lamiaceae), Verbena officinalis (Verbenaceae), Pimpinella anisum, Foeniculum vulgare and Carum carvi (Apiaceae). The germination and radicle growth of tested seeds were affected in different ways by the oils. Thyme, balm, vervain and caraway essential oils were more active against both germination and radicle elongation.
Keywords: essential oils; phytotoxicity; germination; seedling growth; monoterpenes